Tuneable catechin functionalisation of carbohydrate polymers. (1st August 2017) - Oliver, Susan; Jofri, Aziidah; Thomas, Donald S.; Vittorio, Orazio; Kavallaris, Maria; Boyer, Cyrille
Highlights: Catechin was successfully conjugated to three carbohydrate polymers: dextran sodium alginate and chitosan The degree of catechin functionalisation could be easily tuned by varying the acid concentration in the reaction mixture. Catechin functionalisation levels of up to 48% were achieved The structure of all polymers and conjugates was elucidated by 1 H, 1 H- 13 C HSQC and DOSY NMR. All three conjugates showed superior free-radical scavenging activity compared with the non-functionalised polymers. Abstract: In this contribution, we present a strategy to functionalise three natural carbohydrate polymers (dextran − a neutral polymer, sodium alginate − an anionic polymer and chitosan − a cationic polymer) with catechin with excellent degrees of functionality. In a first step, the carbohydrate polymers were oxidised by sodium periodate to yield aldehyde functionalised carbohydrate polymers. The presence of aldehyde groups was exploited to attach catechin by an acid catalysed nucleophilic reaction. The degree of catechin functionalisation could be easily tuned by varying the acid concentration in the reaction mixture, achieving catechin functionalisation levels of up to 48% for dextran aldehyde catechin, 35% for chitosan-aldehyde-catechin and 22% for sodium alginate aldehyde catechin. 1 H, 1 H- 13 C HSQC and DOSY NMR were performed to elucidate the structural differences between the three aldehyde functionalised polysaccharides and how this affects their reactivity and conjugation behaviour. All three carbohydrate polymer-catechin conjugates showed superior free-radical scavenging activity compared with the non-functionalised polymers.